PENGARUH ASIMETRI INFORMASI, CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN PADA MANAJEMEN LABA - Nariastiti, Ni Wayan; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 9 No 3 (2014), 2014)
This research aims to determine the effect of information asymmetry, corporate governance, and firm size on earnings management of publicly traded companies listed on the Indonesian Stock Exchange. Samples was determined by purposive sampling amounting 65 companies. Data were analyzed by multiple regression. The analysis result that the information asymmetry measured by the bid-ask spread has on earnings management positive influence, corporate governance measured by the rating CGPI have negative  effect, and firm size proxid by total assets have negative on earnings management.
Keywords: Information Asymmetry, Corporate Governance, Firm Size, and Earnings Management.